Exercise-induced cardiac troponin release in middle-aged and older athletes with different degrees of coronary atherosclerosis. (11th May 2022) - Janssen, S; De Vries, F; Mingels, AMA; Kleinnibbelink, G; Hopman, MTE; Mosterd, A; Velthuis, BK; Aengevaeren, VL; Eijsvogels, TMH
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Radboud University Medical CenterAcademic Alliance Fund Maastricht - Nijmegen Background: Current sports medical examinations do not appropriately detect occult coronary atherosclerosis in athletes, whereas coronary atherosclerosis is more prevalent in middle-aged and older athletes compared to physically active controls. Therefore, new diagnostic approaches need to be developed to identify individuals at risk. Cardiac troponin (cTn) is the standard biomarker to assess myocardial injury. Exercise is known to increase cTn concentrations and a delayed recovery of cTn concentrations after exercise cessation is suggested to be indicative of occult obstructive coronary artery disease. We hypothesized that the magnitude of exercise-induced cTn elevations may be associated with the degree of coronary atherosclerosis. Purpose: To compare serial measures of exercise-induced cTnT elevations across middle-aged and older athletes with different degrees of coronary atherosclerosis. Methods: A subgroup of 59 men from the Measuring Athlete's Risk of Coronary events-2 study (MARC-2, n=291) were invited for this add-on study. All participants had undergone a cardiac computed tomography (CT) scan and coronary CT angiography to determine the prevalence and magnitude of coronary atherosclerosis. Athletes were stratified based on the degree of coronary atherosclerosis: I) n=20 with a coronary artery calcium score (CACS) of 0, II) n=20 with CACS ≥300 or ≥75th MESA-percentile, and III) n=19 with a >50% stenosis in any coronary artery, but without ischemia on a stress imaging tests. Participants performed an individualized exercise test (>1 hour, cycling) until volitional exhaustion. High-sensitivity cTnT concentrations were measured at baseline, after 30 minutes of exercise and at 0, 30, 60, 120, and 180 minutes post-exercise. Results: Participants (age 60.8 [57.9-72.6] years, BMI 24.5 [23.9-27.3]) exercised for 76±14 minutes, up to 97.6 [94.4-101.8] % of their expected maximum heart rate. Exercise duration and workload did not differ across groups. Baseline hs-cTnT was detectable in everyone. Exercise induced a 1.98±1.63 fold increase in hs-cTnT concentrations. Peak hs-cTnT concentrations occurred at 180 minutes post-exercise (13.9 [9.4-17.0] ng/L versus 12.1 [10.0-21.5] ng/L versus 13.8 [9.1-19.9] ng/L, for group I, II and III, respectively) and the incidence of hs-cTnT concentrations above the URL (n=9 (45%) vs n=7 (35.0%) vs n=9 (47.4%)) was comparable across groups (p=0.92 and p=0.71, respectively). Patterns of time-dependent changes in hs-cTnT concentrations did not differ across groups (p=.49). Conclusion: Exercise-induced elevations in hs-cTnT concentrations did not differ among middle-aged and older athletes with different degrees of coronary atherosclerosis. Our findings suggest that hs-cTnT sampled before, during or within 180 minutes following an exhaustive endurance cycling exercise test is not suitable to detect occult coronary atherosclerosis in athletes.